A study on evaluation systems for optimized design GSHP and ES technologies used in HVAC systems. (24th February 2021) - Zhou, Ruifang; Gong, Dejian; Zhu, Shengjie; Ma, Jianchao; Chen, Jiufa
Abstract: Due to the lack of suitable evaluation systems for heating, ventilation, air-conditioning (HVAC) systems with ground source heat pump (GSHP) and energy storage (ES) technologies, it is difficult to design a building HVAC system to achieve optimized design with regard to investment cost, energy saving and environmental protection. This is a study on developing a fuzzy evaluation system by including GSHP and ES with comprehensively determined weights into an HVAC system. A questionnaire method was used and the answers from 21 HVAC experts were analyzed to facilitate the modeling. Taking a commercial integrated project in Nanjing as an engineering case, the evaluation system was tested. If the system with a comprehensive merit value of 0.303 is adopted, the annual operating cost is reduced by 32.5%, the annual total life cycle cost is reduced by 26.5% and the primary energy consumption and carbon emissions are reduced by 10.5%, with the initial investment increased by 6.5%. This study revealed that the newly developed evaluation system is very useful for realizing the optimal design of HVAC systems.